Manajemen Strategi Pendidikan dalam Meningkatkan Mutu dan Daya Saing Lembaga Pendidikan - Nurani; Safitri Agustina; Samsul Hadi; Nirva Diana; Aan Komariah; Badrudin (WISE Pendidikan Indonesia, 2026)
Educational institutions are increasingly required to strengthen quality, innovation, accountability, and competitiveness in response to policy changes, technological transformation, and growing public expectations. This study aims to analyze and synthesize recent empirical findings on educational strategic management in improving the quality and competitiveness of educational institutions. An integrative literature review was employed by examining peer-reviewed empirical articles published between 2024 and 2026. The selection process began with 86 identified articles, followed by year-based screening, duplicate removal, title and abstract screening, methodological eligibility assessment, and journal indexing verification, resulting in seven final articles that met the inclusion criteria. The analysis was conducted through thematic synthesis by extracting key information related to research focus, institutional context, method, major findings, contribution to quality improvement, and contribution to institutional competitiveness. The findings reveal that educational strategic management contributes to institutional quality and competitiveness through several interconnected dimensions, namely strategic planning, quality culture, principal leadership, human resource management, school-based management, digital transformation, institutional differentiation, accreditation, and continuous evaluation. The synthesis indicates that educational quality is not merely determined by administrative compliance or academic outcomes, but by the institution’s capacity to build sustainable quality culture, professional teacher performance, adaptive governance, innovation, and public accountability. Institutional competitiveness is also shaped by the ability to create distinctive, relevant, and sustainable educational value. The implication of this study is that school leaders, education managers, foundations, supervisors, and policymakers need to design strategic management practices that are integrated, data-informed, participatory, adaptive, and oriented toward continuous quality improvement.